The impact of child Marriage: Challenges to achieving Indonesia's 2045 goals - Rozak, Fakih Abdul; Rizka Isnur Aviana (Jurnal Anifa: Studi Gender dan Anak, 2024)
Child marriage has far-reaching consequences that overshadow the future of Indonesia's younger generation. Meanwhile, the government is vigorously pursuing the vision of Indonesia Gold 2045, an aspiration to make this country advanced, independent, and prosperous. Unfortunately, the practice of early marriage hinders the achievement of this goal. Therefore, this study aims to analyze the implications of child marriage on the discourse of Indonesia Gold 2045, examined from family law, economic law, and state administrative law. This qualitative research uses library research as the data collection method. Furthermore, this study employs a normative-sociological approach and utilizes a descriptive-analytical method. The nature of this research is descriptive-qualitative. The results show that serious efforts must be made to improve and harmonize all existing regulations to avoid misunderstandings and differences of opinion in applying regulations. For Indonesia to achieve its 2045 vision, synergy between the government, society, and families is needed. First, we must have a clear and firm legal system as well as comprehensive sex education to protect the younger generation. Second, there needs to be a strengthening of moral and ethical values in society. Finally, the role of parents is crucial in providing education and supervision to children so that they grow into a quality generation capable of facing future challenges. Therefore, to realize Indonesia Gold 2045, a strong synergy between the government and society in various fields is required. With commitment and good cooperation, Indonesia can achieve its goal of becoming an advanced and prosperous nation.